Dietary n-6 and n-3 PUFA alter the free oxylipin profile differently in male and female rat hearts. Issue 3 (14th August 2019) - Ferdouse, Afroza; Leng, Shan; Winter, Tanja; Aukema, Harold M.
Abstract: Oxylipins are bioactive lipid mediators synthesised from PUFA. The most well-known oxylipins are the eicosanoids derived from arachidonic acid (ARA), and many of them influence cardiac physiology in health and disease. Oxylipins are also formed from other n -3 and n -6 PUFA such as α -linolenic acid (ALA), EPA, DHA and linoleic acid (LA), but fundamental data on the heart oxylipin profile, and the effect of diet and sex on this profile, are lacking. Therefore, weanling female and male Sprague–Dawley rats were given American Institute of Nutrition (AIN)-93G-based diets modified in oil composition to provide higher levels of ALA, EPA, DHA, LA and LA + ALA, compared with control diets. After 6 weeks, free oxylipins in rat hearts were increased primarily by their precursor PUFA, except for EPA oxylipins, which were increased not only by dietary EPA but also by dietary ALA or DHA. Dietary DHA had a greater effect than ALA or EPA on reducing ARA oxylipins. An exception to the dietary n -3 PUFA-lowering effects on ARA oxylipins was observed for several ARA-derived PG metabolites that were higher in rats given EPA diets. Higher dietary LA increased LA oxylipins, but it had no effect on ARA oxylipins. Overall, heart oxylipins were higher in female rats, but this depended on dietary treatment: the female oxylipin:male oxylipin ratio was higher in rats provided the ALA compared with the DHA diet, with other diet groups having ratios in between. In conclusion, individual PUFA and sex have unique and interactive effects on the rat heart free oxylipin profile.